GANGGUAN PEMBENTUKAN ATAP BUMBUNG NEURAL EMBRIO MENCIT AKIBAT INDUKSI 2-ME YANG BERTEPATAN DENGAN MASA NEURULASI PRIMER - Eko Prihiyantoro; Win Darmanto; Samekto Wibowo; Mammed Sagi; Sri Kadarsih Soedjono (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2008)
The objective of this study was to determine time of neural fold fusion at dorsal mid line neural axis after treatment 2-methoxyethanol (2-ME) to pregnant mouse during neurulation period and to observe relation process of point of neural fold fusion. Mice at 08:05 gestational days treatment with 2-ME dose 7.5 mmol/kg bw on the other hand control group injected with aqua bidest. Pregnant mice at 08:12, 09:00, 09:12 was sacrificed by dislocation cervix. Embryo was collected after observe with dissecting microscope for external morphology and fixation in Bouin solution and buffer formalin for histological preparation and immunohistochemistry process. Result showed that there was failure of first point neural fold fusion at junction of perspective fore brain and mid brain. The failure of neural fold fusion was caused by increasing apoptosis neuroepithelium. There were no relation process between first point of neural fold fusion and second point or another point of fusion. Failure of first point fusion not cause failure another point of fusion. Observation at 09:12 gestational days showed that the only first point fusion was still open but formation of another part neural tube have finished.